The Black Circle Bk 5 - Carman, Patrick (New York : Scholastic, 2009)
The two kids were last seen in Egypt, hunting for one of the 39 Clues that could make them the most powerful people on earth. But no one has seen the siblings since. Has the ruthless Irina Spasky finally tracked them down? Or worse-- the Madrigals?
Keywords: Families -- Juvenile fiction; Secret societies -- Juvenile fiction; Code and cipher stories; Brothers and sisters -- Juvenile fiction; Adventure stories; Families -- Fiction; Secret societies -- Fiction; Ciphers -- Fiction; Brothers and sisters -- Fiction; Adventure and adventurers -- Fiction; Mystery and detective stories; Russia -- Juvenile fiction; Russia -- Fiction